The transition from training to work roles : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Garstang, Ashaan (Massey University, 2021)
Joining the RNZAF (Royal New Zealand Air Force) is a significant career commitment and navigating through the early phases of this can be a daunting process. Training prepares newcomers to take on junior work roles and the relative success of this onboarding process will be influenced by the newcomer, depending on their personal growth, competence, and social integration. The aim of this study is to examine the experiences of newcomers who have transitioned through this process and to investigate the factors that made this easier or harder for them. 5 Logistics Operators were interviewed for the study. They had all completed recruit training and the logistics operator (junior) course, and were in an early work role. A qualitative methodology (thematic analysis) was used to gain and examine the data. Themes were broadly categorised into developing competence and overcoming social challenges. The development of competence was dependant on the relevance of training, the ability for newcomers to control their own workplace role, and the reliability of their workplace norms and expectations. Social challenges were managed through the building of workplace relationships, having the ability and confidence to seek clarity from supervisors, and the feeling of social integration within the wider organisation. Outcomes of this study may increase our knowledge of organisational socialisation as it applies within a military context.
Figures 1 and 2 are re-used with permission.
Keywords: 520104 Industrial and organisational psychology (incl. human factors)